Evaluación de la resistencia mecánica y propiedades térmicas de un eco-compuesto de r-pet con fibras de cannabis Sátiva (2023)
Cannabis Sativa (CS) is a plant with potential utilities and inherent properties to obtain different types of products in the industrial and health sectors. Below, the results of the study of the mechanical and thermal properties of an eco-composite material with an R-PET matrix with CS fiber reinforcement, in a proportion of 20% and 30% fiber.